Pengembangan Sumber Daya Manusia pada Produktivitas Kerja di Puskesmas - Puspita Deasy Rahmadiany; Deo Apringga Ayu Nanta; Purwadhi Purwadhi (Syntax Corporation Indonesia, 2024)
All individuals who operate actively and professionally in the health sector are considered health human resources, regardless of whether they have earned formal health education or not. The purpose of this study is to ascertain the Health Center's HR management implementation strategy. This study employed a descriptive qualitative methodology. Purposive sampling, nonprobability sampling, or a sampling strategy based on particular criteria were used to choose the study participants. Documentation, interviews, and observation are some of the data collection techniques. The study's findings show that the HR development management communication components and the recommendations for the Health Center HR development policy have been successfully applied. Even with the improvement in quality, there are still a number of barriers preventing resources from being used efficiently.